(untitled) (European Journal of Health Research, 2024)
Introduction: COVID-19 was one of the greatest crises that the population has suffered, causing illness and death, forcing confinement to try to stop this virus. It produced serious effects on mental health, including the presence of anxious processes among university students. Objective: Identify the emotional disturbance of an anxious type in students in the health area during the restrictions due to the COVID-19 pandemic, in 2021. Method: Descriptive, transversal. The sample was 350 university students. Administering a sociodemographic characterization sheet and the Manifest Anxiety Scale for University Students AMAS-C. Supported under the law regarding research in Mexican territory. Results: Female participation of 77.7%. Ages ranging between 18 and 38 years. 64.0% presented some type of emotional or physical affectation. 74.0% presented extreme global anxiety, where the distribution behaviors between men and women are similar. By dimensions, 94.4% presented significant restlessness and/or hypersensitivity, 78.3% extreme physiological anxiety, 33.4% significant exam anxiety and 24.3% expected levels of social concerns and/or stress. Conclusion: The confinement experienced by these students was identified as the main trigger for the presence of anxiety. It is important that educational, governmental and health authorities provide them with knowledge and tools to face serious situations that threaten their mental health.